Biomarkers for Zoonotic Visceral Leishmaniasis in Latin America - Brodskyn, Claudia I.; Kamhawi, Shaden (Frontiers in Cellular and Infection Microbiology, 2018)
In Latin America, zoonotic visceral leishmaniasis (ZVL) arising from infection by L. infantum is primarily transmitted by Lutzomyia longipalpis sand flies. Dogs, which are chronic reservoirs of L. infantum, are considered a significant risk factor for acquisition of ZVL due to their close proximity to humans. In addition, as a vector-borne disease the intensity of exposure to vector sand flies can also enhance the risk of developing ZVL. Traditionally, IFN-γ and IL-10 are considered as the two main cytokines which determine the outcome of visceral leishmaniasis. However, more recently, the literature has demonstrated that different mediators, such as lipid mediators (PGE-2, PGF-2 alfa, LTB-4, resolvins) and other important inflammatory and anti-inflammatory cytokines are also involved in the pathogenicity of ZVL. Analysis of a greater number of mediators allows for a more complete view of disease immunopathogenesis. Additionally, our knowledge has expanded to encompass different biomarkers associated to disease severity and healing after specific treatments. These parameters can also be used to better define new potential targets for vaccines and chemotherapy for ZVL. Here, we will provide an overview of ZVL biomarkers identified for both humans and dogs and discuss their merits and shortcomings. We will also discuss biomarkers of vector exposure as an additional tool in our arsenal to combat ZVL.